Strategi Marketing Dalam Mempertahankan Loyalitas Nasabah Pada Produk Simpanan Deposito di BMT UGT Cabang Pembantu Kraksaan - Maula Nasrifah; Kamilah Rihadatul Aisya (Jurnal Manajemen dan Bisnis, 2021)
This study aims to describe and determine marketing strategies in maintaining customer loyalty on deposit products at BMT UGT Sidogiri Kraksaan Sub-Branch. Besides that, the aim of this study is to find out what achievements and obstacles exist in BMT UGT Kraksaan sub-branch in maintaining customer loyalty. This research use desciptive qualitative approach. The results of this study are the marketing strategy used by BMT UGT Sidogiri Kraksaan sub-branch, which prioritizes employee friendliness and responsiveness, where in this study the responsive attitude shown by BMT UGT Sidogiri Kraksaan sub-branch is always accommodating complaints from customers for the good of BMT in the future.